Contamination with Toxocara sp eggs and health assessment of parks in the city of Abancay, Peru - Cáceres Pinto, Cori Milagros (2017)
The aim of this study was to determine the association between contamination with Toxocara sp and the sanitary classification of parks of the Department of Food Hygiene and Zoonosis, Ministry of Health (Peru), in the city of Abancay, Peru. The research was analytical, basic level and cross-sectional. Sampling (n=276) was conducted in all 21 city parks through a systematic random sampling using the double «W» methodology. The classification of parks was carried out using the assessment sheet of the Park Sanitary Surveillance Programme, assessing the infrastructure, environment, and health risks. The results showed that 66.7% of parks were contaminated with Toxocara sp and the frequency of samples contaminated with the parasite was 26.8% (95% CI = 21.4-32.2). None of the parks qualified as friendly, 38.1% were considered less friendly and 61.9% as not friendly. The evaluation form of the Park Sanitary Surveillance Programme was not applicable to estimate the contamination with Toxocara sp.